2014
DOI: 10.1186/1477-7819-12-206
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open resection for gastric gastrointestinal stromal tumors: an updated systematic review and meta-analysis

Abstract: BackgroundIn past decades, laparoscopic surgery has been introduced for the treatment of gastrointestinal stromal tumors (GISTs). Recently, additional studies comparing laparoscopic versus open surgery for gastric GISTs have been published, and an updated meta-analysis of this subject is necessary.MethodsA systematic search was conducted in PubMed, Embase, Cochrane Library, and Web of Science. Comparative studies of laparoscopic and open surgery for gastric GISTs published before June 2014 were identified from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Metaanalyses of comparative retrospective series suggested that the laparoscopic approach be proposed for smaller-diameter tumors, which yielded a similar operation time and favored a laparoscopic approach with its decreased intraoperative blood loss, and earlier recovery including time to first flatus, time to oral feeding, and decreased length of stay. [6][7][8][9][10][11] Conflicting data were reported regarding postoperative morbidity and oncologic results that were either similar or even better in the laparoscopic group, with a marginal impact on medical complications and a similar risk of surgical and grade III-IV complications. [6][7][8][9][10][11] From a methodological perspective, a meta-analysis of nonrandomized cohorts with no allocation concealment carries a potential risk of overstating the intervention effect by 30%-41%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Metaanalyses of comparative retrospective series suggested that the laparoscopic approach be proposed for smaller-diameter tumors, which yielded a similar operation time and favored a laparoscopic approach with its decreased intraoperative blood loss, and earlier recovery including time to first flatus, time to oral feeding, and decreased length of stay. [6][7][8][9][10][11] Conflicting data were reported regarding postoperative morbidity and oncologic results that were either similar or even better in the laparoscopic group, with a marginal impact on medical complications and a similar risk of surgical and grade III-IV complications. [6][7][8][9][10][11] From a methodological perspective, a meta-analysis of nonrandomized cohorts with no allocation concealment carries a potential risk of overstating the intervention effect by 30%-41%.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9][10][11] Conflicting data were reported regarding postoperative morbidity and oncologic results that were either similar or even better in the laparoscopic group, with a marginal impact on medical complications and a similar risk of surgical and grade III-IV complications. [6][7][8][9][10][11] From a methodological perspective, a meta-analysis of nonrandomized cohorts with no allocation concealment carries a potential risk of overstating the intervention effect by 30%-41%. 18 In addition to the problem of the tumor size that clearly influences both the surgical technique and prognosis, most studies were not designed for oncologic purposes with missing or inconsistent data regarding the mitotic index or TKI administration and a limited follow-up.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent retrospective analysis of patients treated by laparoscopic resection of GISTs between 2002 and 2012, the 5-year recurrence-free survival was 63% in high-risk patients whereas it was 100% at 10 years in the low- and very-low-risk groups, indicating that laparoscopic surgery may be performed with similar results as open resection [47]. A recent meta-analysis of 22 studies comparing laparoscopic versus open surgery for GISTs including 1,166 patients demonstrated improved short-term results (intraoperative blood loss, onset of gastrointestinal motility, time to oral intake, hospital stay and overall complications) in the laparoscopic group [48]. However, one of the major pitfalls of surgery for GISTs is the risk of intraoperative tumor rupture, conferring a recurrence rate of almost 100% [49].…”
Section: Management Of Localized Gistsmentioning
confidence: 99%
“…The third one, comprising 12 articles and 644 patients concludes that laparoscopic surgery was associated with a reduction in intraoperative blood loss, earlier resumption of oral intake and shorter duration of hospital stay over the short-term, and with a significantly lower rate of overall recurrence, metastatic and local recurrence in the long-term compared to open surgery (Ohtani et al, 2013). The fourth one, of 22 studies including 1,166 patients concludes that laparoscopic surgery for gastric GISTs is acceptable for selective patients (Chen et al, 2014). Lastly, one of 19 studies and 1,060 cases concludes that laparoscopic approach had better results in terms of blood loss, postoperative morbidity (POM) and recovery .…”
Section: Introductionmentioning
confidence: 99%